1995
DOI: 10.1103/physrevb.51.7946
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic reaction mechanisms in hydrogen-loaded germanosilicate fibers: Formation of divalent Ge defects

Abstract: We have investigated the microscopic mechanisms for the thermal reactions of H2 with germanosilicate optical fibers by means of first-principles quantum chemical techniques. As a first reaction step, it has recently been shown that H2 reacts with a Ge -0 bond to form Ge -H and SiO -H. In this work, we have carefully considered the activation energies for two additional reaction channels at the Ge -H site which lead to divalent Ge defects. A channel involving hydrogen migration from Ge to a neighboring 0 is fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…7,8 The Raman spectral data by Greene et al 6 identified a few of the important products of chemical reactions between H 2 and germanosilicate fibers such as wSiO-H, wGe-H ͑monohydride͒, and vGeH 2 ͑dihy-dride͒. 7,8 We obtained transition states and the associated activation barriers of some of the reaction sequences to identify those with relatively smaller energy barriers. 7,8 We obtained transition states and the associated activation barriers of some of the reaction sequences to identify those with relatively smaller energy barriers.…”
Section: Reactions Of Divalent Ge In Hydrogen Loaded Germanosilicate mentioning
confidence: 99%
See 3 more Smart Citations
“…7,8 The Raman spectral data by Greene et al 6 identified a few of the important products of chemical reactions between H 2 and germanosilicate fibers such as wSiO-H, wGe-H ͑monohydride͒, and vGeH 2 ͑dihy-dride͒. 7,8 We obtained transition states and the associated activation barriers of some of the reaction sequences to identify those with relatively smaller energy barriers. 7,8 We obtained transition states and the associated activation barriers of some of the reaction sequences to identify those with relatively smaller energy barriers.…”
Section: Reactions Of Divalent Ge In Hydrogen Loaded Germanosilicate mentioning
confidence: 99%
“…The possible reaction paths leading to the above products were investigated by first-principle quantum chemical calculations in our previous papers. 8 It is generally accepted that the 240 nm absorption band in germanosilicate fibers is due to germanium oxygen deficiency centers ͑GODC͒ and a likely candidate for GODC is the divalent Ge defect. As a first step, the reaction occurs at a Ge site where a Ge-O bond is broken by H 2 to form wGe-H and wSiO-H. 7 A subsequent hydrogen migration from Ge to a neighboring O can lead to the formation of divalent Ge defects.…”
Section: Reactions Of Divalent Ge In Hydrogen Loaded Germanosilicate mentioning
confidence: 99%
See 2 more Smart Citations
“…It is clear that in both FBG writing processes the writing laser creates defects in the glass network. In the case of the UV modification of silica-based glass fibers, much work has been done on identifying the kinds of defects generated [8][9][10].…”
Section: Introductionmentioning
confidence: 99%